2014
DOI: 10.1002/ccd.25347
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the MitraClip® system for severe mitral regurgitation

Abstract: MitraClip® implantation for moderate to severe or severe MR appears to be safe with a very low procedural mortality. There is significant improvement in functional outcomes although long-term mortality is high, especially in high surgical risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 32 publications
7
36
0
1
Order By: Relevance
“…In another study by Schäfer et al17 examining the impact of preprocedural LV ejection fraction on the outcome of MitraClip therapy in 393 patients with functional mitral regurgitation, the authors found a significant increase in 6MWT, which was most pronounced in those with an LV ejection fraction >40% (+69.8±103.3 meters) followed by those with an LV ejection fraction of 10% to 20% (61.1±150.3 meters). In a meta‐analysis of 2980 patients, Vakil et al19 found an increase in 6MWT from 261±14 meters at baseline to 360±25 meters at follow‐up. In our study, 6MWT increased from 160±116 to 267±132 meters.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Schäfer et al17 examining the impact of preprocedural LV ejection fraction on the outcome of MitraClip therapy in 393 patients with functional mitral regurgitation, the authors found a significant increase in 6MWT, which was most pronounced in those with an LV ejection fraction >40% (+69.8±103.3 meters) followed by those with an LV ejection fraction of 10% to 20% (61.1±150.3 meters). In a meta‐analysis of 2980 patients, Vakil et al19 found an increase in 6MWT from 261±14 meters at baseline to 360±25 meters at follow‐up. In our study, 6MWT increased from 160±116 to 267±132 meters.…”
Section: Discussionmentioning
confidence: 99%
“…Major complications reported from the EVEREST II trial and a four-year MitraClip follow up study include major bleeding, stroke or transient ischemic attack, chordal rupture, pericardial tamponade and myocardial infarction; endocarditis, however, was not one of the reported complications in the landmark EVEREST II trial [18,19]. There have been only a few reported cases of patients with infective endocarditis in the region of the MitraClip [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…0.1%), while its long-term rate increased by 15.8%. It should be noted that the mortality rate as a side effect of the Mitraclip is related to the patient's risk level; therefore, safety is significantly different in high-risk and lowrisk groups (10).…”
Section: Discussionmentioning
confidence: 99%